APPLICATION OF SWEDISH MASSAGE ON THE ANXIETY LEVEL OF MINOR PRE-OPERATIVE PATIENTS - Supri; Amrih Widiati (Universitas Bina Bangsa Getsempena, 2024)
Background: Anxiety is the most common problem experienced by preoperative patients. Excessive anxiety before surgery can have negative impacts such as changes in the patient's hemodynamics which can result in delays in the operation. Objective: To determine the application of Swedish massage to the anxiety level of patients pre-minor surgery. Method: This type of research uses descriptive case studies. This research was conducted on May 20 2024 at IBS, a private hospital in Semarang City. The subjects of this writing are two preoperative patients who experienced moderate anxiety. The instrument used to measure anxiety levels is the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Results: Measurement of the level of anxiety before being given Swedish massage was that the first subject experienced moderate anxiety with an APAIS score of 20 and the second subject experienced moderate anxiety with an APAIS score of 21. After being given the Swedish massage intervention, there was a decrease in the level of anxiety from moderate to mild, namely the subject with an APAIS score of 13 and the second subject with an APAIS score of 14. Conclusion: Swedish massage can be used as an alternative in treating anxiety in preoperative patients.